2022
DOI: 10.3390/foods11203154
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability Analysis of 3D-Printed Food in the Area of the Czech Republic Based on Survey

Abstract: The aim of the research was to observe consumer perceptions of 3D food printing and to highlight possible applications of this production. The questionnaire survey took place in the Czech Republic and was attended by 1156 respondents. The questionnaire was divided into six sections: (1) Socio-Demographic Data; (2) 3D Common Printing Awareness; (3) 3D Food Printing Awareness; (4) 3D Food Printing, Worries and Understanding; (5) Application; (6) Investments. Although awareness of 3D food printing is increasing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The questionnaire, structured into nine sections, addressed attitudes based on Menozzi et al [ 21 ], Sultan et al [ 72 ], Tesikova et al [ 73 ], and Govaerts and Olsen [ 74 ]; subjective norms based on Sultan et al [ 72 ] and Chen [ 75 ]; perceived behavioral control following Sultan et al [ 72 ] and Lee et al [ 51 ]; sensory appeal derived from Imtiyaz et al [ 76 ]; food neophobia following Pliner and Hobden [ 77 ], Siegrist et al [ 50 ], Jaeger et al [ 78 ], and Lee et al [ 51 ]; perceived health risk based on Hwang and Choe [ 79 ] and Tesikova et al [ 73 ]; environmental friendliness following Verain et al [ 80 ]; and behavioral intentions derived from Lee et al [ 51 ] and Tesikova [ 73 ] and demographic variables. Each variable was assessed using a seven-point Likert scale, allowing respondents to express their perspectives authentically.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire, structured into nine sections, addressed attitudes based on Menozzi et al [ 21 ], Sultan et al [ 72 ], Tesikova et al [ 73 ], and Govaerts and Olsen [ 74 ]; subjective norms based on Sultan et al [ 72 ] and Chen [ 75 ]; perceived behavioral control following Sultan et al [ 72 ] and Lee et al [ 51 ]; sensory appeal derived from Imtiyaz et al [ 76 ]; food neophobia following Pliner and Hobden [ 77 ], Siegrist et al [ 50 ], Jaeger et al [ 78 ], and Lee et al [ 51 ]; perceived health risk based on Hwang and Choe [ 79 ] and Tesikova et al [ 73 ]; environmental friendliness following Verain et al [ 80 ]; and behavioral intentions derived from Lee et al [ 51 ] and Tesikova [ 73 ] and demographic variables. Each variable was assessed using a seven-point Likert scale, allowing respondents to express their perspectives authentically.…”
Section: Methodsmentioning
confidence: 99%
“…Having that said, many believe consumers' views regarding 3DPFs will improve as they learn more about them and/or have more exposure to them. According to a survey study by Tesikova et al (2022), most respondents believed that food printing would be used in the food industry since 3DPFs are aesthetically pleasing. We are also of the view that consumer acceptance of 3D-printed edibles will improve, especially if more sensitization goes into the concept of 3D food printing and possible food safety concerns around them are addressed.…”
Section: Shape Fidelitymentioning
confidence: 99%
“…Since this technology is new, there has been some difficulty in getting consumers to accept 3DPFs. Research studies have shown that consumers tend to have food neophobia or fear of experimenting with new cuisines/food products (Lee et al, 2021; Tesikova et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond nutrition: consumer acceptance, cost-effectiveness, food safety, ethics and regulations determine three-dimensional food printing adoption Similar to many other innovations, the real-world adoption of 3D food printing technology depends on consumer acceptance. Only a few empirical studies have investigated consumer attitudes (including allied health professionals) towards 3D food printing in different settings (32,66,(88)(89)(90)(91)(92)(93)(94) , with some recently summarised by Baiano (5) . In general, the studies find that consumers have low awareness and knowledge about 3D food printing, suggesting that consumer acceptance of 3D food printing may be challenging due to unfamiliarity with the technology, while some consumers believe 3D-printed food is 'unnatural' and are concerned of its health benefits (5) .…”
Section: Sensory Manipulations Using Three-dimensional Food Printing ...mentioning
confidence: 99%